Evaluating Severe Therapy-Resistant Asthma in Children: Diagnostic and Therapeutic Strategies - Andrew Bush (Medicina)
Introduction: Worldwide, asthma is the most common non-communicable respiratory disease and causes considerable morbidity and mortality. Most people with asthma can be treated effectively with low-dose medications if these are taken correctly and regularly. Around 10% of people with asthma have an uncontrolled form of the disease or can only achieve control with high-dose medications, incurring disproportionately high health care costs. Areas Covered: PubMed and personal archives were searched for relevant articles on the definition, management and pharmacotherapy of severe asthma. The WHO classification of severe asthma and the treatment levels encompassed in the definition are discussed. Most children and young people referred for consideration of ‘beyond-guidelines therapy’ can in fact be managed on standard treatment after a multi-disciplinary team assessment focusing on ensuring correct basic management, and these steps are described in detail. Options for those with true therapy-resistant asthma are described. These include monoclonal antibodies, most of which target type 2 inflammation. Expert Opinion: Getting the basics right is still the most important aspect of asthma care. For those with severe, therapy-resistant asthma, an increasing number of life-transforming monoclonals have been developed, but there is still little understanding of, and a paucity of treatment options for, non-eosinophilic asthma.